Methodological identification of opportunities for development of smart specialization in Pomorskie Voivodship in Poland - Dorota Kamrowska-Zaluska; Jacek Soltys (European Regional Science Association (ERSA), 2014)
Smart specialization as a concept plays a more and more important role in development of the regions. David, Foray and Hall point it, as an important instrument for creating a strategy for the development of innovation at the state and regional level as well as for defining and building the knowledge-based economy. This term is present in a number of strategic development documents in the European Union, including Europe 2020, published by the European Commission in 2010. It implies the need for countries and regions to specialize as well as focus development of innovation in areas that are consistent with their endogenous potentials. This paper presents the method as well as results of the studies undertaken to define the smart specialization of Pomerania, which is one of two Polish voivodeships with access to the Baltic Sea. Its main settlement node is the emerging metropolitan area of Gdansk - the fourth largest in Poland. Part of this research was project Identification of Smart Specialization in Pomerania Voivodeship - Technological Convergence, commissioned by the Regional Government. Technological convergence was defined as phenomenon of the use of technologies from different industries for the creation of a new specialization in order to gain a competitive advantage. The aim of the project was to analyze and evaluate the economic potential of the Voivodeship, indicating possible areas of cooperation between representatives of different industries. It was assumed that the process of identifying smart specialization would be a bottom-up approach. Regional Government invited all actors to build a partnership. They worked on identifying potentials then building on this analysis, developed a common strategy for the development of technological and functional smart specialization. Analytical and diagnostic processes included: desk research, expert studies, individual in-depth interviews, focus group interviews, workshops and the Delphi study, SWOT analysis. The result is an aid for all stakeholders to identify opportunities and specify areas of development of smart specializations for the Voivodship. The method of identification of the priorities and implementation of the actions for the development of smart specializations assumes that the process itself should be flexible, meaning that adopted priorities and allocation of resources need to be reviewed and modified if such need occurs. The authors also present their recommendation to enhance this method; propose its modification and expansion to include e.g. conduct the Competitive Position Analysis of Porter's Five Forces.
Keywords: O2; O3; O38; 330; smart specialization; technological convergence; Pomeranian Voivodeship; regional knowledge-based development; innovation strategy